1997
DOI: 10.1007/s002130050281
|View full text |Cite
|
Sign up to set email alerts
|

Non-functional CYP2D6 alleles and risk for neuroleptic-induced movement disorders in schizophrenic patients

Abstract: The use of classic anti-psychotic drugs in the long-term treatment of schizophrenia is associated with risk for extrapyramidal side-effects, such as akathisia, parkinsonism and tardive dyskinesia (TD). Approximately 5-10% of European Caucasians lack the cytochrome P450 enzyme CYP2D6 (so-called poor metabolizers; PM), which normally metabolizes several drugs including many neuroleptics. PM subjects may achieve high or toxic plasma levels upon standard drug therapy. In this study we have examined 100 subjects fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 38 publications
(47 reference statements)
2
53
0
Order By: Relevance
“…Nine studies 58,60,70,76,78,88,89,96,97 clearly specified the number of missing genotypes and six of these provided reasons for the missing data. 58,60,70,76,78,96 In the remaining 42/51 studies, it was unclear whether the number contributing to each analysis was equal to the sample size.…”
Section: Clinical Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies 58,60,70,76,78,88,89,96,97 clearly specified the number of missing genotypes and six of these provided reasons for the missing data. 58,60,70,76,78,96 In the remaining 42/51 studies, it was unclear whether the number contributing to each analysis was equal to the sample size.…”
Section: Clinical Validitymentioning
confidence: 99%
“…Nine studies 58,60,70,76,78,88,89,96,97 clearly specified the number of missing genotypes and six of these provided reasons for the missing data. 58,60,70,76,78,96 In the remaining 42/51 studies, it was unclear whether the number contributing to each analysis was equal to the sample size. No study mentioned conducting specific tests for population stratification even though six 57,60,87,96,102,103 were known to include patients with different ethnic backgrounds.…”
Section: Clinical Validitymentioning
confidence: 99%
“…As patients were assessed only once, the TD diagnosis in our sample corresponds to the category of 'cross-sectional TD'. [36][37][38] Association of HSPG2 with TD in Caucasians…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is unclear what range of effect sizes the studies were powered to detect. 126 Andreassen 1997, 127 Armstrong 1997, 128 Arranz 1995, 129 Arthur 1995, 130 Brockmoller 2002, 131 Culav-Sumic 2001, 132 de Leon 2004, 133b Dettling 2000, 134 Ellingrod 2000, 135 Ellingrod 2002, 136 Ellingrod 2002, 137 173 However, when studies reporting significant outcomes were subsequently analysed, around half had adequately given reasons for the specific alleles tested.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…In terms of the included studies, it was not always apparent from the manner in which data were reported whether any genotype data were missing. Some studies (n = 9) 127,139,145,146,148,152,153,162,164 clearly specified the number of missing genotypes and two-thirds of these 127,139,146,152,153,164 provided reasons for the missing data. All but two studies 142,171 gave the number of patients contributing to each analysis.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%